Mission Batak traditions to Educational Transformation: The History, Dynamics, and Challenges of Church Schools in Tapanuli, 1950-2024 - Pestaria Naibaho (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2026)
This study examines the historical transformation, institutional dynamics, and contemporary challenges of church-based education in Tapanuli, North Sumatra, Indonesia, from 1950 to 2024. Although missionary education played a foundational role in the development of formal schooling and Christian leadership among the Batak, the post-independence trajectory of church schools has received comparatively limited attention as a process of institutional transformation. This study employed a qualitative historical research design using archival documents, published historical sources, oral histories, field observations, and material evidence. The findings demonstrate that church-based education underwent three major transformations: the transition from missionary education to an Indigenous church-based educational system after independence; institutional professionalization and adaptation to national educational structures; and contemporary transformation in response to educational competition, technological change, professional standards, and cultural expectations. The study further demonstrates that Batak communities actively appropriated educational institutions as instruments of literacy, social mobility, leadership formation, and “hamajuon” (social progress). However, tensions remain between inherited Western educational epistemologies and the need to strengthen Batak cultural and Indigenous knowledge within Christian education. The study concludes that the future relevance of church schools depends on integrating theological identity, educational quality, technological innovation, and culturally responsive pedagogy. Church schools should therefore be understood as dynamic institutions of educational, ecclesial, cultural, and social transformation.